2019
DOI: 10.22159/ijcpr.2019v11i4.34931
|View full text |Cite
|
Sign up to set email alerts
|

Mental Ill-Health and Heart Failure Comorbidity

Abstract: This review aims to understand the co-existence of mental ill-health and heart failure and if this comorbidity affects patient self-care motivation and overall health outcomes. Databases searched were; PubMed®, Google® scholar and Science Direct® for studies related to heart failure, heart failure and mental health, depression and anxiety. Eleven articles were identified and reviewed. There were two studies disagreed with the theory that the mental ill-health and heart failure has disease modification and wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…IBs correlate significantly and positively to stress, where beliefs are not rational as mediators in the relationship between stressors and stress. Stress disturbs the homeostatic equilibrium of the body and makes individuals susceptible to diseases [19] and also in line with a theory that there is the link between the continuing development of heart disease and depression with chronic stress [20]. The high IBs score of Balinese women can not only result in decreased work productivity but can also result in an increased risk of chronic stress, depression, and even suicide.…”
Section: Purnawati Et Almentioning
confidence: 81%
See 1 more Smart Citation
“…IBs correlate significantly and positively to stress, where beliefs are not rational as mediators in the relationship between stressors and stress. Stress disturbs the homeostatic equilibrium of the body and makes individuals susceptible to diseases [19] and also in line with a theory that there is the link between the continuing development of heart disease and depression with chronic stress [20]. The high IBs score of Balinese women can not only result in decreased work productivity but can also result in an increased risk of chronic stress, depression, and even suicide.…”
Section: Purnawati Et Almentioning
confidence: 81%
“…Persons with IBs show a different perspective on themselves, real stressors, and the world they face. Those could create of increase a tendency to feel distressed and being hopeless [20,21].…”
Section: Purnawati Et Almentioning
confidence: 99%
“…This meta-analysis demonstrates that depression is associated with poor cardiac outcomes in patients with coronary artery disease. Depression is widespread in patients with cardiovascular disease and must be screened for throughout the management plan to ensure that their mental health does not have an impact on their cardiovascular outcomes [24]. Systematic review of the available data, combined with statistical analysis, demonstrated that multidisciplinary collaborative care reduces major adverse cardiac outcomes significantly in patients with cardiovascular diseases (CVD).…”
Section: Systematic Review Conclusionmentioning
confidence: 99%
“…The current socio-demographic distribution of HF and the past 28-year trend around the world deserve special focus as the recent trend shows that changes in worldwide HF case distribution, though the burden of HF is still largely prevalent in middle to high SDI regions and which would increase the further burden in low to middle SDI regions by reversing the current scenario [1][2][3][4][5]. This will impose additional challenges to low-income countries toward attaining anticipated outcomes with their poor health-care infrastructure availability, access, and quality [22], and severe economic burden on virtually every country around the world by staggering costs related to HF, which are mainly due to repeated hospitalizations and the loss of productivity in patients with HF [31,32]. This requires the implementation of welltailored health-care services to facilitate the unsustainable burden in local health-care systems particularly in low-income countries.…”
Section: Trends In Hfmentioning
confidence: 99%